2023
DOI: 10.3390/ijms241914504
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on the Effect of Nitrogen on Rapeseed between Seed Yield and Oil Content and Its Regulation Mechanism

Jiarong Zhu,
Wenjun Dai,
Biyun Chen
et al.

Abstract: Rapeseed (Brassica napus L.) is one of the most important oil crops in China. Improving the oil production of rapeseed is an important way to ensure the safety of edible oil in China. Oil production is an important index that reflects the quality of rapeseed and is determined by the oil content and yield. Applying nitrogen is an important way to ensure a strong and stable yield. However, the seed oil content has been shown to be reduced in most rapeseed varieties after nitrogen application. Thus, it is critica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…The previous study demonstrated that seed oil was synthesized through triacylglycerols including several metabolic pathways, such as the Calvin cycle, C assimilation, and starch metabolism [ 45 ]. In contrast, seed protein synthesis was associated with N uptake, transportation, and lipid synthesis [ 46 ]. The stronger inhibition of salt stress on C assimilation than on N assimilation led to a concentration effect for N, resulting in an increase in N content.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study demonstrated that seed oil was synthesized through triacylglycerols including several metabolic pathways, such as the Calvin cycle, C assimilation, and starch metabolism [ 45 ]. In contrast, seed protein synthesis was associated with N uptake, transportation, and lipid synthesis [ 46 ]. The stronger inhibition of salt stress on C assimilation than on N assimilation led to a concentration effect for N, resulting in an increase in N content.…”
Section: Discussionmentioning
confidence: 99%
“…Rapeseed, a Brassica plant of the Cruciferae family, is the third largest oilseed crop in the world and the largest in China, with the oil, vegetable, and owers used as food, tea, and fertilizer. China has approximately 20% of the word's rapeseed production area (USDA FAS, 2023) and produces 5.2 million t of high-quality edible oil annually, accounting for about 50% of domestic edible vegetable oil (Zhu et al, 2023). As a fertilizer-dependent crop, oilseed rape has higher nutrient requirements for nitrogen, phosphorus and other nutrients than crops such as wheat and soybean (Fang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%